2014
DOI: 10.1519/jsc.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Acute Prior Heavy Strength Exercise Bouts Improve the 20-km Cycling Time Trial Performance

Abstract: This study verified if a prior 5 repetition maximum (5RM) strength exercise would improve the cycling performance during a 20-km cycling time trial (TT20km). After determination of the 5RM leg press exercise load, 11 trained cyclists performed a TT20km in a control condition and 10-minute after 4 sets of 5RM strength exercise bouts (potentiation condition). Oxygen uptake, blood lactate concentration, ratings of perceived exertion (RPE), and power output data were recorded during the TT20km. Cycling economy ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 23 publications
5
40
1
1
Order By: Relevance
“…This combination, which significantly increased VO 2peak , effectively circumvented any interference to strength development over 12 weeks of concurrent training. In this regard, the increase in absolute VO 2peak observed with CET is in line with previous literature [ 15 , 21 23 , 61 , 67 70 ]. However, relative VO 2peak was only increased from baseline at WK6 in CET, while END demonstrated improvements from baseline at both WK6 and POST.…”
Section: Discussionsupporting
confidence: 93%
“…This combination, which significantly increased VO 2peak , effectively circumvented any interference to strength development over 12 weeks of concurrent training. In this regard, the increase in absolute VO 2peak observed with CET is in line with previous literature [ 15 , 21 23 , 61 , 67 70 ]. However, relative VO 2peak was only increased from baseline at WK6 in CET, while END demonstrated improvements from baseline at both WK6 and POST.…”
Section: Discussionsupporting
confidence: 93%
“…Instead of using a time-based cycling trial (Martin et al, 2016 ), we used a mental fatigue paradigm in a distance-based cycling trial, a laboratory trial (i.e., TT 20km ) traditionally used in scientific investigations (Silva et al, 2014 ; Pinheiro et al, 2016 ). We preferred a trial closed by distance as this may represent a more realistic condition met in cycling competitions and training sessions (Abbiss et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, different from a recent mental fatigue study using a 20 min time-based cycling trial to investigate cyclists we preferred to use a distance-based trial, as this may represent a more realistic condition met in cycling competitions and training sessions. Moreover, we wanted to use a distance which has already been previously investigated, thus making possible inferences to cycling literature (Silva et al, 2014 ; Pinheiro et al, 2016 ). The TT 20km filled these requirements, being a long-endurance trial which may potentiate mental fatigue effects on physical performance (Van Cutsem et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, there is paucity of data on the effects of CHO mouth rinse on shorter-lasting trials such as 4 km (TT 4km ). Although most cycling literature has focused on long- (i.e., 40 km and 20 km) [ 3 , 9 , 11 , 12 ] as well as short-lasting time trials (TT 4km ) [ 13 , 14 ] when investigating manipulations to potentiate cycling performance, evidence for the potential benefit of the CHO mouth rinse in short-lasting cycling time trial performance has yet to be provided. For example, a previous study reported that CHO mouth rinse attenuated global fatigue in an endurance cycling trial, despite the unchanged performance.…”
Section: Introductionmentioning
confidence: 99%